REKAYASA PERANGKAT LUNAK ALAT KENDALI JEMURAN OTOMATIS MENGGUNAKAN ARDUINO DAN SENSOR HUJAN/AIR, KELEMBABAN DHT11 DAN CAHAYA LDR - Anju Parapat; Syaechurodji Syaechurodji (Jurnal Ilmiah Sains dan Teknologi, 2020)
This study aims to describe, analyze and design a control tool that can help secure clothesline at home left by the owner so that it does not get rained on, even though it seems simple but if this tool is designed properly and correctly it will be able to provide benefits for its users, because it is able to work Automatically uses sensors to detect cloudy weather, humidity and rain drops. This tool is able to work automatically hide clothes in a safe location so as not to be exposed to rain, when the tool detects weather that is not sunny or about to rain, not only that when the device detects clear weather then the clothes that had been hidden in a place protected from rain water will be re-placed in locations exposed to sunlight automatically return.